Penatalaksanaan Terapi Komplementer dan Alternatif secara Holistik untuk Meningkatkan Pemberdayaan Keluarga pada Penyakit Menahun - Muhlisoh (Jurnal Pengabdian Masyarakat Eka Prasetya, 2022)
According Dinas Kesehatan Kabupaten Banjar data, hypertension and diabetes mellitus are the most common in this area. Hypertension and diabetes mellitus are chronic diseases that most suffer from community members in Kabupaten Banja. In providing nursing care to residents who suffer from chronic diseases, it is necessary to increase nurses' confidence in nursing values ​​which are the guidelines and foundations in providing nursing-care, which must be embedded both in individuals, families and communities. Health not only expected but also to be fit for people that apart from being healthy. The holistic concept is the basis and goal of complementary and alternative medicine for individuals or citizens. Complementary and Alternative Therapy is a non-conventional treatment aimed at improving the degree of public health in dealing with chronic illnesses suffered. Results of short interviews with 10 villagers, there were 8 residents who said they often feel bored in taking medicine because it has been too long, so the family needs to provide support. Based on the data above, the author team seeks to improve the health status of the community and is very important in order to achieve a better standard of living. Strategies to achieve health status. The objective of activity is to implement screening of complementary and alternative therapy management to residents, so that local health workers can follow up the problem that’s happen.